Public Service - Bintang Muhammad Faan Tarigan; Nur Fauzi (AT-TAFAHUM: Journal of Law, 2020)
Public service is one of the main indicators of the quality of government administration and the fulfillment of basic rights of the people by the state. As public demands for fast, transparent, and quality services increase, the government is required to improve the public service system through the application of good governance principles, bureaucratic reform, and technology-based service innovation. This study aims to analyze the dynamics of public services in the context of modern government administration, specifically the factors that influence service quality and efforts to improve it. The research method used is a qualitative study with a library research approach, with data obtained from accredited national scientific journals, reference books, and relevant official documents from the last five years. The research stages include determining the focus of the study, collecting library materials, and descriptive-analytical data analysis. The results show that the quality of public services is significantly influenced by the application of the principles of transparency, accountability, fairness, and professionalism of the apparatus. In addition, bureaucratic reform, service innovation, strengthening human resource capacity, and the use of digital technology have been proven to increase the effectiveness, efficiency, and public satisfaction with public services. This research is expected to provide theoretical contributions to the development of public administration science and practical recommendations for improving the quality of public services in Indonesia.